The proteomics and metabolomics studies of GZU001 on promoting the Merisis of maize (Zea mays L.) roots - Zheng, Zhiguo; Chen, Shunhong; Wei, Panpan; Guo, Shengxin; Yu, Gang; Wu, Jian (BMC plant biology, 2023)
Plant growth regulators are chemicals that regulate plant growth and development, which can regulate hormonal balance and affect plant growth, thereby increasing crop yield and improving crop quality. Our studies have revealed a new compound, GZU001, which could be used as a plant growth regulator. This compound has been observed to affect root elongation in maize significantly. However, the exact mechanism of this phenomenon is still being investigated. Metabolomics and proteomics were used in unison in this study to explore the response pathway and regulation mechanism of GZU001 in promoting maize root elongation. From the appearance, we can see that both roots and plants of maize treated with GZU001 are significantly improved. Maize root metabolism revealed 101 differentially abundant proteins and 79 differentially expressed metabolites. The current study identified altered proteins and metabolites associated with physiological and biochemical processes. GZU001 treatment has been demonstrated to promote primary metabolism, essential for carbohydrates, amino acids, energy, and secondary metabolism. The result suggests that the stimulation of primary metabolism is beneficial for the growth and development of maize and plays a significant role in sustaining metabolism and growth. This study recorded the changes of related proteins and metabolites in maize roots after GZU001 treatment and provided evidence for this compound's action mode and mechanism in plants.